2013
DOI: 10.5469/neuroint.2013.8.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Coil Embolization of Distal Anterior Cerebral Artery Aneurysms: Angiographic and Clinical Follow-up Results

Abstract: PurposeThis study is an overview of the clinical and angiographic outcomes of patients who undergo treatment for distal anterior cerebral artery aneurysms.Materials and MethodsBetween January 2009 and March 2012, 444 cerebral aneurysms were treated using endovascular coil embolization at our institute. Among them, 217 aneurysms were followed-up with angiography at least six months later. Of these, there were 16 distal anterior cerebral artery (ACA) aneurysms in 16 patients. We conducted a retrospective review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
3
13
2
Order By: Relevance
“…(3,20) However, we did see a very high proportion of major recanalizations (12 of 13 cases; 92.3%). In two other recently-reported series, (21,22) much lower rates of major recanalizations were reported, i.e., 16% and 25%, but we note that the populations of those studies, respectively 16 and 23 patients, were smaller than ours (92 patients).…”
Section: Discussioncontrasting
confidence: 84%
“…(3,20) However, we did see a very high proportion of major recanalizations (12 of 13 cases; 92.3%). In two other recently-reported series, (21,22) much lower rates of major recanalizations were reported, i.e., 16% and 25%, but we note that the populations of those studies, respectively 16 and 23 patients, were smaller than ours (92 patients).…”
Section: Discussioncontrasting
confidence: 84%
“…3,9,17,19,20 Therefore, we need to be aggressive, without complication, even Sturiale demonstrated in a systematic review a rate nearly 7% of overall periprocedural rupture, with a procedure related morbidity rate of 8%, higher than that of other circle of Willis aneurysms. 7,[21][22][23] Comparing the technical challenges posed by the endovascular management and clipping, both techniques present difficulties. Pericallosal artery aneurysms at the bifurcation represent a special endovascular technical challenge given their distal location, commonly wide-neck morphology, small parent vessel diameter and potentially high recurrence rate after coiling given the bifurcation location.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that treatment with endovascular coiling caused a higher re-bleeding risk than surgical clipping in the International Subarachnoid Aneurysm Trial, 22) and DACA aneurysms tended to recur more often than with aneurysms in other locations. 23,24) We found that reoperation was needed in five cases of recanalization, but re-bleeding was not encountered. Endovascular coiling requires careful follow-up compared with surgical clipping.…”
Section: Discussionmentioning
confidence: 91%